Albuminuria but not low eGFR is closely associated with atherosclerosis in patients with type 2 diabetes: an observational study - Jun-Wei Wang; Jiang-Feng Ke; Zhi-Hui Zhang; Jun-Xi Lu; Lian-Xi Li (Diabetology & Metabolic Syndrome, 2022)
Abstract Background There is still controversy regarding the associations of urinary albumin excretion (UAE) and estimated glomerular filtration rate (eGFR) with atherosclerosis in patients with type 2 diabetes mellitus (T2DM). Therefore, it is necessary to explore the correlation between them in T2DM patients. Methods We conducted a survey involving 2565 T2DM patients from a single center. The study cohort was classified into three groups based on the levels of albuminuria: normal UAE (UAE < 30 mg/24 h), moderate UAE (UAE between 30 and 299 mg/24 h) and high UAE (UAE ≥ 300 mg/24 h). Additionally, the patients were divided into three separate groups according to eGFR levels, including low eGFR (eGFR < 60 ml/min/1.73 m2), intermediate eGFR (eGFR 60–89 ml/min/1.73 m2) and normal eGFR (eGFR ≥ 90 ml/min/1.73 m2) groups. Atherosclerotic lesions were compared among the three UAE and eGFR groups. Regression analyses were used to assess the associations of atherosclerotic lesions with UAE and eGFR in T2DM. Results After controlling for age, sex and diabetes duration, the prevalence of atherosclerotic plaque and stenosis were significantly increased from the normal to high UAE groups (plaque: 72.2%, 78.6% and 87.3%, respectively, p = 0.016 for trend; stenosis: 14.0%, 25.5% and 37.3%, respectively, p < 0.001 for trend). Likewise, the values of carotid intima-media thickness (CIMT) and femoral intima-media thickness (FIMT) were also obviously increased from the normal to high UAE groups (CIMT: p < 0.001 for trend; FIMT: p = 0.001 for trend). Conversely, only the FIMT value was clearly increased from the low to normal eGFR groups (p = 0.001 for trend). Fully adjusted regression analyses revealed that UAE was closely associated with the presence of atherosclerotic plaque (OR 1.20, 95% CI 1.03–1.40, p = 0.020) and stenosis (OR 1.17, 95% CI 1.01–1.35, p = 0.036), and with the values of CIMT (β 0.05, 95% CI 0.01–0.10, p = 0.029) and FIMT (β 0.07, 95% CI 0.03–0.11, p = 0.001) in T2DM patients. However, there was no significant association between eGFR levels and atherosclerotic lesions in T2DM after adjustment for multiple confounding factors. Conclusions Overall, albuminuria rather than low eGFR is closely associated with atherosclerotic lesions in T2DM patients. Albuminuria is an independent risk factor for carotid and femoral atherosclerotic lesions in T2DM. Therefore, albuminuria may be a potential early marker to predict the development of atherosclerosis in patients with T2DM.